Self-organization networking technology for 5G ultra-dense wireless network - Jiandong LI; Min SHENG; Junyu LIU; Chenxi ZHAO; Yan ZHANG; Hongguang SUN (物联网学报)
Enhancing network capacity by increasing the density of the fifth-generation wireless networks has become one of the key challenges for the future mobile systems.A practical channel model for ultra-dense network (UDN) was built,and the limitation of network densification by analyzing the interference distribution was revealed.To approach the limit,UDN-oriented self-organization networking (SON) technology was proposed and its new feature in UDN was investigated.Finally,a SON based cell merging and splitting strategy was tailored.Experiment results indicate that the proposed strategy is capable for improving network capacity and user experience significantly.